The Role of E-Commerce Platforms in Enhancing Digital Literacy For 21st-Century Learning Among University Students - Diah Laila Wulan; Anjar Sulistiyani; Anggi Fitri Hasanah; Juhdan Abdulloh Muarif; Sofie Nur Haqiqi Baetillah; Dea Nur Fatimah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
The rapid development of digital technology has brought significant changes across various aspects of life, including education and economic activities. One manifestation of this technological advancement is the emergence of e-commerce platforms, which facilitate online buying and selling. Among university students, e-commerce is used not only to meet daily needs but also to enhance digital literacy. This study aims to examine the role of e-commerce platforms in improving students’ digital literacy as part of 21st-century learning. The research employs a library research method by collecting and analyzing various literature sources, including scientific journals, books, and relevant articles. The findings indicate that e-commerce usage helps students develop critical thinking skills, particularly in searching for, evaluating, and selecting accurate and reliable information. In addition, e-commerce encourages students to be more creative, communicate effectively in digital spaces, and collaborate through online interactions. Therefore, e-commerce platforms play a vital role in enhancing students’ digital literacy and developing 21st-century skills, especially critical thinking, creativity, collaboration, and communication (4C).